Calmodulin Affects Sensitization of Drosophila melanogaster Odorant Receptors - Mukunda, Latha; Miazzi, Fabio; Sargsyan, Vardanush; Hansson, Bill S.; Wicher, Dieter (Frontiers in Cellular Neuroscience, 2016)
Flying insects have developed a remarkably sensitive olfactory system to detect faint and turbulent odor traces. This ability is linked to the olfactory receptors class of odorant receptors (ORs), occurring exclusively in winged insects. ORs form heteromeric complexes of an odorant specific receptor protein (OrX) and a highly conserved co-receptor protein (Orco). The ORs form ligand gated ion channels that are tuned by intracellular signaling systems. Repetitive subthreshold odor stimulation of olfactory sensory neurons sensitizes insect ORs. This OR sensitization process requires Orco activity. In the present study we first asked whether OR sensitization can be monitored with heterologously expressed OR proteins. Using electrophysiological and calcium imaging methods we demonstrate that D. melanogaster OR proteins expressed in CHO cells show sensitization upon repeated weak stimulation. This was found for OR channels formed by Orco as well as by Or22a or Or56a and Orco. Moreover, we show that inhibition of calmodulin (CaM) action on OR proteins, expressed in CHO cells, abolishes any sensitization. Finally, we investigated the sensitization phenomenon using an ex vivo preparation of olfactory sensory neurons (OSNs) expressing Or22a inside the fly’s antenna. Using calcium imaging, we observed sensitization in the dendrites as well as in the soma. Inhibition of calmodulin with W7 disrupted the sensitization within the outer dendritic shaft, whereas the sensitization remained in the other OSN compartments. Taken together, our results suggest that CaM action is involved in sensitizing the OR complex and that this mechanisms accounts for the sensitization in the outer dendrites, whereas further mechanisms contribute to the sensitization observed in the other OSN compartments. The use of heterologously expressed OR proteins appears to be suitable for further investigations on the mechanistic basis of OR sensitization, while investigations on native neurons are required to study the presently unknown additional mechanisms involved in OSN sensitization.